2013
DOI: 10.1002/ajmg.b.32134
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA (mtDNA) in brain samples from patients with major psychiatric disorders: Gene expression profiles, MtDNA content and presence of the MtDNA common deletion

Abstract: Several lines of evidence support a mitochondrial dysfunction in major psychiatric disorders. The objective of this study was to determine whether mitochondrial DNA (mtDNA) expression or content are implicated in the mitochondrial dysfunction observed in schizophrenia (SCH), bipolar disorder (BD), and major depressive disorder (MDD). MtDNA gene expression and mtDNA content (including the MT-ND4 deletion) were measured by RT-qPCR and qPCR, respectively. Post-mortem brain tissue from 60 subjects, divided evenly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 74 publications
2
40
0
Order By: Relevance
“…The present results are in accordance with three studies in BD postmortem brains which showed no alteration in mtDNA content Sabunciyan et al, 2007;Torrell et al, 2013). In contrast with our findings, one study found that mtDNA content slightly increased in post-mortem BD subjects (Vawter et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present results are in accordance with three studies in BD postmortem brains which showed no alteration in mtDNA content Sabunciyan et al, 2007;Torrell et al, 2013). In contrast with our findings, one study found that mtDNA content slightly increased in post-mortem BD subjects (Vawter et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…Although mtDNA encodes ETC proteins which lower its transcription in BD (Konradi et al, 2004;Sun et al, 2006), evidence challenges the association between mtDNA content and mtDNA transcription (Torrell et al, 2013;Vawter et al, 2006). Rather, it is possible that mtDNA sequence plays a more crucial role in mtDNA expression (Reinecke et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mtDNAcn has been reported to be significantly high in autism (Giulivi et al 2010), significantly reduced in some (but not in all) studies on bipolar disorder (Chang et al 2014, de Sousa et al 2014, Kakiuchi et al 2005, Sabunciyan et al 2007, Torrell et al 2013, Vawter et al 2006) and positively associated with childhood adversity and lifetime psychopathology in healthy people (Tyrka et al 2015). A recent study in community-dwelling women (n=142) found significantly lower mtDNAcn in people with higher depressive symptoms (not necessarily diagnosed with Major Depressive Disorder [MDD]) compared to those with lower depressive symptoms (Kim M. Y. et al 2011).…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Numerous studies have reported that deletions of mitochondrial DNA (mtDNA) have a vital role in aging and acquired impairment in various human organs, including the brain, heart, liver, skin, skeletal muscle and cornea (4)(5)(6). Cochlea tissue is rich in mtDNA, which have a high probability of deletion.…”
Section: Introductionmentioning
confidence: 99%